2021
DOI: 10.3390/ijms22052272
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Lipidomics for the Determination of Phospholipid and Eicosanoid Profiles in Atlantic Salmon (Salmo salar L.) Muscle Tissue Using Electrospray Ionization (ESI)-MS/MS Spectrometric Analysis

Abstract: Shotgun lipidomics was applied to identify and quantify phospholipids (PLs) in salmon muscle tissue by focusing on the distribution of ω-3 fatty acids (e.g., docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)) in the form of phospholipids, as well as to identify and quantify eicosanoids, which has not yet been attempted in Atlantic salmon muscle. Shotgun lipidomics enabled the identification of 43 PL species belonging to four different classes: phosphatidylcholines (PCs), phosphatidylethanolamines (PEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Lipidomic approaches are currently used to characterize the polar and non-polar lipid profiles of marine edible fish, such as anchovy (Engraulis sp. ), 155 gilthead sea bream (Sparus aurata), 156 obscure pufferfish (Takifugu fasciatus), 157 salmon (Salmon salar), 155,[158][159][160][161] seahorse (Hippocampus spp. ), 162 and tuna (Tunnus spp.).…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipidomic approaches are currently used to characterize the polar and non-polar lipid profiles of marine edible fish, such as anchovy (Engraulis sp. ), 155 gilthead sea bream (Sparus aurata), 156 obscure pufferfish (Takifugu fasciatus), 157 salmon (Salmon salar), 155,[158][159][160][161] seahorse (Hippocampus spp. ), 162 and tuna (Tunnus spp.).…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
“…165 DI-MS approaches also provided significant information to elucidate the effects of diet and genetic background on TG and PL metabolism in Atlantic salmon muscle tissue. 160,161 Marine mammals have recently been the subject of some lipidomic studies, which were focused on the cetacean family (whales, dolphins and porpoises). These studies performed the first comprehensive characterization of the lipid profile of the plasma, 166,167 heart, 168 and adipose tissue (i.e., blubber).…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmon has become one of the three largest farmed fish worldwide due to its desirable nutritional effects, and it occupies a wide range of domestic and international consumer markets. Salmon phospholipids are rich in n‐3 polyunsaturated fatty acids (PUFAs), which can reduce triglyceride (TG) levels and suppress CVD and obesity‐associated metabolic disorders such as chronic inflammation, insulin resistance and dyslipidemia 5‐7 . Meanwhile, it has been reported that the intake of n‐3PUFAs from fish in the diet has the effect of reducing risk of CVD, MetS, cancer, Parkinson's disease and inflammation, and the optimal dietary intake of n‐3PUFAs in seafood is 250 mg (200–300) per day 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Salmon phospholipids are rich in n-3 polyunsaturated fatty acids (PUFAs), which can reduce triglyceride (TG) levels and suppress CVD and obesity-associated metabolic disorders such as chronic inflammation, insulin resistance and dyslipidemia. [5][6][7] Meanwhile, it has been reported that the intake of n-3PUFAs from fish in the diet has the effect of reducing risk of CVD, MetS, cancer, Parkinson's disease and inflammation, and the optimal dietary intake of n-3PUFAs in seafood is 250 mg (200-300) per day. 8,9 Lipids are the main components of cell membranes and play a vital role in maintaining membrane structure and function, participating in signal transduction, providing energy storage and transporting substances.…”
Section: Introductionmentioning
confidence: 99%